A Unique Government–NGO–Industry Partnership Care Model to Reduce Morbidity and Mortality Among Underprivileged Children With Type 1 Diabetes Mellitus in LMIC: A Pilot Study From Tamil Nadu, India - Krishnan Swaminathan; Suruliappan Sopnajothi; Krishnamurthy Nidharshana; Govindasamy Prakash (Journal of Diabetology)
Aim: To pilot a 1-year comprehensive type 1 diabetes mellitus program, assessing outcomes on glycemic control and diabetic ketoacidosis (DKA) admissions pre- and post-intervention in underprivileged children with type 1 diabetes mellitus from three selected Government Medical College Hospitals across Tamil Nadu state, through a Government–nongovernmental organization (NGO)–Industry partnership.